The Fabrication of Local Identity: Marginalization of the Indigenous Dayak Beverage in Central Kalimantan - Sofyan Ansori (Laboratorium Bantenologi UIN Sultan Maulana Hasanuddin Banten, 2018)
Abstract Since the decentralization era that started in 1999, the need to search for local identity in various regions in Indonesia gradually emerged. Local elites have been pursuing some specific characteristics to legitimize their indigeneity and authenticity which are useful to strengthen their local power grip. The production of local identity (e.g., adat; tradition) was transformed into a key factor for the success of a local government in the transition of political and economic power in Indonesia (Bourchier, 2007; Erb, 2007). In that cultural production, a particular ethnic tradition was often fabricated into a binary dichotomy; “good” and “bad” to come up with a “true local identity.” Within this scheme, a tradition considered “bad” is rejected. Baram, a traditional Dayak beverage containing alcohol, faces this kind of rejection. Even though it is inherently a part of the Dayak culture, evidence of its existence is systematically deleted in the public domain such as museums, books, and public documents and other local publications. Baram is perceived as a form of bad habit and also is thought to be irrelevant to the contemporary Dayak identity that is struggling to eliminate the stereotype of being uncivilized. This paper argues that the marginalization of baram not only is a matter of politics but also is related to current social and cultural contestation in Central Kalimantan, Palangkaraya in particular. The analysis in this paper focuses on the relation of the Dayak as indigenous people of Central Kalimantan and migrants from other Kalimantan regions and outside of Kalimantan. The data were collected during my short ethnographic research in Palangkaraya and Katingan Regency, Central Kalimantan in 2015. Baram is suspected of being a source of overconsumption of alcohol that triggers violence and criminal actions in both urban and rural communities. Such a formulation is common in the mass media to describe the negative effects of baram. The marginalization of baram continues and has escalated into a more serious matter as the local regime now labels it as illegal good. It is, thus, alienated in its own home.